The Effect of Global Warming on Electricity Generation and Electronic Devices - Nagham Mahmood Aljamali; Asmaa Kefah Mahdi; Noorhan Ali Hamza (Journal of Power Electronics and Devices, 2021)
The effect of global warming on the generation of electricity and electronic devices is the effect resulting from the generation of electric power as a result of global warming, although it contributes as power plants to cause severe damage to the environment due to the burning of raw materials such as coal, fuel, and oil. These materials are extracted from the ground in general, and this happens when materials are burned, and a gas containing toxic materials such as carbon dioxide is produced. Some of these gases resulting from the combustion of raw materials cause global warming, which directly contributes to the increase in global warming. This combustion also causes great pollution to the air that humans and other organisms inhale, which puts their health at risk. Also, this air in the atmosphere is not the only one we inhale, as there are plants and animals, all of which are directly affected. Fuel is burned and electricity is used very heavily in developed countries relative to developing countries, some of which is caused by global warming, but since the environmental damage does not only harm us but harms everyone, society must cooperate and maintain a clean environment.